Enhancing people centered service delivery - Uganda Women’s Network (Uganda Women’s Network, 2013)
By definition, service delivery is getting services as effectively and quickly as possible to the intended recipient. The main objective of service delivery is to ensure physical, emotional and social needs are met and that people live and function as independently as possible within their own communities. The aim of the Policy brief is to contribute to debates on the strengths and weaknesses of social service delivery in Uganda. People–centered and integrated services are critical for reaching universal social service coverage. People– centered service is service that is focused and organized around the social needs and expectations of people and communities. In addition, the relationship between government and citizens is crucial. Ultimately, government is accountable to citizens for decisions taken. Many countries need to improve the substantive elements of democracy and its checks and balances to ensure that public goods are delivered according to citizens’ expectations.